Safety and feasibility of robotic-assisted thoracic surgery after neoadjuvant chemoimmunotherapy in non-small cell lung cancer - Zeng, Jun; Yi, Bin; Chang, Ruimin; Chen, Yufan; Yu, Zhongjie; Gao, Yang (Frontiers in Oncology, 2023)
OBJECTIVES: This study aimed to evaluate the safety and feasibility of robotic-assisted thoracic surgery (RATS) after neoadjuvant chemoimmunotherapy in NSCLC. METHODS: We retrospectively collected data for NSCLC patients who received thoracic surgery after neoadjuvant chemoimmunotherapy from May 2020 to August 2022. Surgery details, pathological response, and perioperative outcome were compared between a video-assisted thoracic surgery (VATS) group and RATS group. Inverse probability of treatment weighting (IPTW) was used to balance the baseline characteristics. RESULTS: A total of 220 patients were divided into 78 VATS patients and 142 RATS patients. There was no 90-day mortality in either group. RATS patients demonstrated better results in conversion rate to thoracotomy (VATS vs. RATS: 28.2% vs. 7.5%, P < 0.001), number of lymph node stations harvested (5.63 ± 1.75 vs. 8.09 ± 5.73, P < 0.001), number of lymph nodes harvested (13.49 ± 9.325 vs. 20.35 ± 10.322, P < 0.001), yield pathologic-N (yp-N) upstaging (yp-N0, 88.5% vs. 67.6%; yp-N1, 7.6% vs. 12.6%; yp-N2, 3.8% vs. 19.7%; P < 0.001), and visual analog scale pain score after surgery (4.41 ± 0.93 vs. 3.77 ± 1.21, P = 0.002). However, there were no significant differences in pathological response evaluation for neoadjuvant chemoimmunotherapy (P = 0.493) and complication rate (P = 0.803). After IPTW-adjustment, these results remained constant. CONCLUSIONS: RATS reduced the risk of conversion to thoracotomy, provided a better yp-N stage evaluation, and improved pain score; this suggests that RATS is safe and feasible for NSCLC patients after neoadjuvant chemoimmunotherapy.